A GRAMMATICAL STUDY OF FOREGROUNDING IN SELECTED POEMS FROM PHILIP LARKIN, THE ENGLISH POET - Kadhim, Saad Badi; Hussein, Ahmed Sultan (Journal of Social Comunity Services, 2026)
Objective: This study aims to explore the grammatical foregrounding in Philip Larkin's poetry, focusing on how this stylistic device attracts readers' attention, and to propose an eclectic model for analyzing foregrounded expressions. Method: A qualitative approach was used, analyzing selected poems from Larkin through frameworks by Quirk et a and Rajimmwale. The analysis examines various types of foregrounding, including ellipsis, rhetorical questions, and metaphor. Results: The study identifies predominant foregrounding techniques in Larkin's poetry, particularly pun and metaphor, and highlights the frequent use of understatement and fronting to emphasize the poet’s themes of pessimism and the futility of life. Additionally, rhetorical questions were found to be less frequent but significant in their role in the poetry’s meaning. Novelty: This work contributes a new eclectic model of foregrounding that combines various theoretical approaches, offering a unique tool for analyzing poetic texts and enriching the understanding of Larkin's stylistic choices.